MAKING OF LIQUID ORGANIC FERTILIZER USING AGRICULTURAL RAW MATERIALS - agus susilo (Journal of Innovation and Applied Technology, 2017)
Agricultural wastes so large numbers still have the potential to be harnessed into a more useful product, including the manufacture of liquid organic fertilizer. Organic fertilizer has great market potential in the future. In this community service activities will be focused on technological improvements liquid fertilizer on partners in Madiun, East Java. Activities that have been made include 1. Development of Business Management, 2. Repair and improvement of business production capacity, 3. Creation of a standardized system of raw materials, 4. Transformation technology to sarasaran. 5. Improved methods of marketing. Use of empowering local resources and assistance to the partner is able to overcome the problems faced by the business groups.